How I Managed to Integrate: An Analysis of the Protective Factors in Determining Good Life Events and Turning Points of Three Former Prisoners in Malaysia - Mohd Alif Jasni; Siti Hajar Abu Bakar Ah; Norruzeyati Che Mohd Nasir (Kajian Malaysia, 2022)
Imprisonment impacts the life events and turning points of former prisoners upon release. The challenges faced during societal re-integration are contributing factors that shape the life events of former prisoners upon release and subsequently determine their turning point. This study aims to prove that positive life events will cause former prisoners to shape positive turning points after release. Criminal justice studies have since strived to understand the factors that cause former prisoners to repeat their crimes after being released from prison. However, in Malaysia, not many works have explored the factors that cause former prisoners to cease committing a crime. Besides, the successful re-integration of these prisoners is still understudied. The researchers conducted a qualitative study in Kuala Lumpur with 19 former prisoners. The results revealed that 16 informants had repeatedly committed crimes, while only three managed to desist. This study will describe the views and experiences of the three former prisoners (desisters) on how they desist from crime during re-integration. Only three desisters were considered and did not include 16 other recidivist informants since the objective of this study was to identify the success factors for re-integration and to understand the protective factors of former prisoners during re-integration into society. The crucial findings were also discussed, including family acceptance, the presence of a supportive spouse, employment, avoiding negative peers, no drug addiction and being healthy. These factors managed to prevent the former prisoners from committing crimes again.